The Influence of Knowledge Sharing, Work Engagement, and Job Autonomy on Innovative Work Behavior of Employees in Multinational Companies - Sonya Sidjabat (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Multinational corporations which lack innovative work behavior will find it impossible to compete against other businesses which operate across international boundaries. The study examines how knowledge sharing and work engagement and job autonomy together impact innovative work behavior of employees in multinational enterprises. The research team establishes an explanatory research framework through its quantitative research methodology. The research team collected data through surveys which included 150 employees who worked at multinational corporations. The research team applied multiple linear regression for data analysis after they had completed validity and reliability tests and classical assumption tests which included assessments of normality and multicollinearity and heteroscedasticity. The study shows that knowledge sharing and work engagement and job autonomy bring positive effects to innovative work behavior because each factor produces separate effects and their combined effects create a coefficient of determination value of 0.79. Organizations can enhance their employees capacity to innovate by implementing initiatives which expand knowledge sharing programs and improve work engagement and provide employees with necessary organizational freedom. The study offers practical human resource management solutions to multinational company management which will lead to improved innovation through knowledge sharing and employee engagement and work flexibility practices. The research expands existing literature on innovative behavior by studying global organizations in this particular context.